Memahami Digital Sculpting dengan Aplikasi Zbrush - Anton Sugito Kurniawan (Humaniora, 2013)
This article discusses how to sculpt digitally with ZBrush software. This is a new trend in film, gaming, and animation industry using 3D modelling software like ZBrush. ZBrush is a digital sculpting tool that combines modeling 3D/2.5D, texturing, and painting. The use of a technology called Pixol on the software allows deep storage of lighting, color, and material information in an object in the layer. Moreover, the technology differs Zbrush with other 3d modeling softwares which are more traditional because the software is more like sculpting. Zbrush as a digital sculpting tool is capable of making high-resolution models (up to ten million polygons). The Zbrush capability at the level of high resolution and detail level can be set dynamically, allowing the user to make changes in total or in part on the carvings. Stages described in the article in addition to explain the function of the tool, are also the advantages that exist in ZBrush software compared to other 3d softwares. Sample images from various sources and some projects may help the reader know and understand the Zbrush software and bridge the manual artist to digital 3d artist as well.